Developing DMD therapeutics: a review of the effectiveness of small molecules, stop-codon readthrough, dystrophin gene replacement, and exon-skipping therapies. (1st February 2021) - Sheikh, Omar; Yokota, Toshifumi
ABSTRACT: Introduction: Duchenne muscular dystrophy (DMD) is an X-linked recessive disorder caused by mutations in the dystrophin (DMD) gene. Most patients die from respiratory failure or cardiomyopathy. There are significant unmet needs for treatments for DMD as the standard of care is principally limited to symptom relief through treatments including steroids. Areas Covered: This review summarizes safety and efficacy in promising areas of DMD therapeutics – small molecules, stop codon readthrough, gene replacement, and exon skipping – under clinical examination from 2015–2020 as demonstrated in the NIH Clinical Trials and PubMed search engines. Expert Opinion: Currently, steroids persist as the most accessible medicine for DMD. Stop-codon readthrough, gene replacement, and exon-skipping therapies all aim to restore dystrophin expression. Of these strategies, gene replacement therapy has recently gained momentum while exon-skipping retains great traction. The FDA approval of three exon-skipping antisense oligonucleotides illustrate this regulatory momentum, though the effectiveness and sequence design of eteplirsen remain controversial. Cell-penetrating peptides promise to more efficaciously treat DMD-related cardiomyopathy.The recent success of antisense therapies, however, poses major regulatory challenges. To fully realize the benefits of exon-skipping, including cocktail oligonucleotide-mediated multiple exon-skipping and oligonucleotide drugs for very rare mutations, regulatory challenges need to be addressed in coordination with scientific advances.